Alteration of Subcellular Beta Catenin Expression in Normal Mucosa Adenoma and Carcinoma in Relation to Colorectal Carcinogenesis - Pamela Damaledo Abineno; Diah Rini Handjari; Budiningsih Siregar (The Indonesian Society for Digestive Endoscopy, 2010)
Background: Adenomatous polyposis coli (APC) gene mutation was found in up to 80% of cases of sporadic colorectal cancers and adenomas. Loss of APC protein function has been known as one of the early process in colorectal carcinogenesis. This event leads to the accumulation of beta catenin in the cytoplasm and nucleus and subsequently activates target genes that regulate cell proliferation and apoptosis. The aim of this study was to investigate the alteration of subcellular beta catenin expression in the progression of colorectal cancer. Method: This cross-sectional study was conducted with 30 paraffin-embedded tissue sections each of normal colorectal mucosa, adenomas and carcinomas. Alteration of beta catenin expression in membranous, cytoplasmic, and nuclear compartments were evaluated by immunohistochemical staining. Results: Beta catenin immunoreactivity was detected in all cases, of which 87 (96.7%) cases showed membranous expression, 78 (86.7%) cases had cytoplasmic and 51 cases (56.7%) had nuclear expression. Such results were statistically significant (p 0.000). All normal colorectal epithelium showed membranous beta catenin expression with 18 (60.0%) cases showed cytoplasmic and no nuclear beta catenin expression was found. Strong cytoplasmic expression was found in 17 (56.7%) adenomas and 25 (83.3%) carcinomas; while strong nuclear expression was found in 12 (40.0%) adenomas and 17 (56.7%) carcinomas. There was no statistical significant association between beta catenin expression in the membranous, cytoplasmic and nuclear compartment with the degree of dysplasia or differentiation of tumor (p 0.05). Conclusion: Altered subcellular expression of beta catenin occurs as the oncogenic process develops from adenoma into carcinoma. Such finding reflects the importance of beta-catenin in colorectal carcinogenesis. Keywords: beta catenin, colorectal cancer, adenoma, colorectal cancer progression